Pengembangan Kemandirian Amal Usaha Pendidikan Muhammadiyah melalui Unimmart.Com Marketplace Gerakan Bedukmutu - Pratolo, Suryo; Anwar, Misbahul; Dewi, Veni Soraya (Universitas Muhammadiyah Yogyakarta, 2022)
ABSTRACTThe COVID-19 pandemic in the industrial revolution 4.0 increasingly encourages the need for the nation's economic independence which is supported by information technology systems. The bedukmutu movement with the unimmart.com marketplace offers a solution to answer these challenges. The bedukmutu movement at Universitas Muhammadiyah Magelang is an entrepreneurial movement based on demand-pull to encourage purchases by campus academics. The activity of buying and selling is an atmosphere that must be created so that universities contribute to realizing economic independence. Unimmart.com is a web-based marketplace application using the IoT (Internet of Things) concept that prioritizes convenience for the millennials. The purpose of this community service is to create an entrepreneurial atmosphere and realize economic independence at Universitas Muhammadiyah Magelang. This community service program implements bedukmutu with the support of the unimmart.com marketplace through three stages: (1) brainstorming with the academics of the Universitas Muhammadiyah Magelang, (2) conducting focus group discussions (FGD) with the academics of Universitas Muhammadiyah Magelang, and (3) developing and socialization of unimmart.com to the academic community. The result of this community service is the creation of the bedukmutu movement with the support of the unimmart.com marketplace at Universitas Muhammadiyah Magelang. In addition to creating an entrepreneurial atmosphere and economic independence for the academic community and the University of Muhammadiyah Magelang as an educational business charity in Muhammadiyah, this community service program is intended to integrate the theory and practice of real entrepreneurship for students.